Exposure to Diazepam during Pregnancy Alters the Breathing Control in Post-Natal Life - da Silva Junior, Carlos Aparecido; Biancardi, Vivian; Alexandre Patrone, Luis Gustavo; Helena Gargaglioni, Luciane (Revista Cubana de Investigaciones Biomédicas, 2020)
Introduction: Breathing is an important motor behavior that contributes to the maintenance of homeostasis. This behavior depends on the proper development of respiratory network located in brainstem that generates and controls the respiratory rhythm during the embryonic and post-natal ages. The development of this network can be affected by the use of psychiatric medications prescribed to mothers to treat general anxiety or panic disorders. One of the most common drugs prescribed is Diazepam (DZP), a benzodiazepine that binds to gamma-aminobutyric acid (GABAA) receptors enhancing the permeability of chloride channels. However, it is still unknown if the administration of DZP during pregnancy could have deleterious effects on breathing control during post-natal life. Objective: To understand the consequences of intrauterine exposure to DZP on the ventilatory responses of newborns rats, Material and Methods: We administered DZP (1mg/Kg) or its vehicle, via osmotic pump, to pregnant rats during whole pregnancy (21 day). We used newborns rats (male and female) at post-natal day 0 (P0) and P12. Ventilation (VE), tidal volume (VT), respiratory frequency (fR) and oxygen consumption (VO2) were measured by using head-out plethysmograph during 20 minutes of normocapnia, hypercapnia (7% CO2) and hypoxia (10% O2). Results: At P0, females treated with DZP had an attenuation of VT during hypoxia. At P12, males and females presented a decrease on VE during hypoxia and VE/VO2 was lower in DZP-treated animals. At this age, hypercapnic ventilatory response was also reduced in DZP groups due to an attenuation of VT. Conclusions: DZP during pregnancy promotes a decrease in ventilatory responses to CO2 and O2 in males and females, and this disturbance occurs at P12 that is considered the critical period for breathing control.